METODE DAKWAH BUYA SAPRIBIL MALIN MARAJO DI SURAU PINANG BELIRIK KAMPUNG MELATI SOREK SATU KABUPATEN PELALAWAN RIAU - Puji Mana Aprila; Yusuf Afandi (Jurnal Komunikasi, 2023)
The da'wah method is a method of da'wah used by a da'i to convey his da'wah and material to mad'u to achieve certain activities. With this da'wah method, a preacher can convey the da'wah material that will be delivered. The author's interest is in wanting to know the method used by Buya Sapribil Malin Marajo so that his preaching can be accepted. And what is known at this time is that a mad'u wants to take part in his preaching studies, especially in the village of Melati Sorek Satu. Therefore, how can Buya Sapribil Malin Marajo invite and protect people in his environment to attend his recitation. The type of research used is qualitative descriptive research which aims to describe research results according to actual data. The informants in this research were divided into two, namely key informants and supporting informants. The key informant was Ustadz Buya Sapribil Malin Marajo, while the supporting informants were mad'u or his congregation. Data collection techniques use observation, interviews and documentation. The preaching methods used by Buya Sapribil to his congregation are the bil-hikmah, mau'idzah hasanah and mujadallah al-lati hiya ahsan methods. The bil-hikmah method is used when he is giving wise examples to the congregation in between the recitations he is delivering. Mau'idzah hasanah is used when giving a statement regarding good advice. Muadallah al-lati hiya ahsan applied the da'wah method he used was question and answer, discussion and interpersonal conversation and this application was very much in line with the da'wah method